Nonlinear physics of ecosystems - Meron, Ehud (CRC Press, Taylor & Francis Group, 2015)
Nonlinear Physics of Ecosystems introduces the concepts and tools of pattern formation theory and demonstrates their utility in ecological research using problems from spatial ecology. Written in language understandable to both physicists and ecologists in most parts, the book reveals the mechanisms of pattern formation and pattern dynamics. It also explores the implications of these mechanisms in important ecological problems.The first part of the book gives an overview of pattern formation and spatial ecology, showing how these disparate research fields are strongly related to one another. T.
Keywords: Biotic communities -- Mathematical models.; Nonlinear theories.; elektronické knihy; electronic books